2020
DOI: 10.1007/s40744-020-00232-5
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil Improves Exercise Tolerance in Systemic Sclerosis Patients with Interstitial Lung Disease: A Pilot Study

Abstract: Introduction: Systemic sclerosis (SSc) is an autoimmune disease characterized by the overproduction of collagen leading to fibrosis of the skin and internal organs. Interstitial lung disease (ILD) is one of the major causes of death in patients with SSc. Exercise tolerance can be investigated by cardio-pulmonary exercise testing (CPET). First-line therapies in patients with SSc associated with ILD (SSc-ILD) include cyclophosphamide and mycophenolate mofetil (MMF). The aim of this study was to evaluate the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…A total of 13 studies were eligible for qualitative synthesis (table 1). [9][10][11][12][13][14][15][16][17][18][19][20][21] Separately, four ongoing MMF studies were identified, including one phase II RCT, two open-label trials and one prospective cohort study; two studies address pulmonary involvement of systemic sclerosis, one study recruits participants with fibrotic hypersensitivity pneumonitis and one study focuses on idiopathic inflammatory myopathy ILD (online supplemental document 3).…”
Section: Search Of Relevant Studiesmentioning
confidence: 99%
“…A total of 13 studies were eligible for qualitative synthesis (table 1). [9][10][11][12][13][14][15][16][17][18][19][20][21] Separately, four ongoing MMF studies were identified, including one phase II RCT, two open-label trials and one prospective cohort study; two studies address pulmonary involvement of systemic sclerosis, one study recruits participants with fibrotic hypersensitivity pneumonitis and one study focuses on idiopathic inflammatory myopathy ILD (online supplemental document 3).…”
Section: Search Of Relevant Studiesmentioning
confidence: 99%